Dampak Pariwisata Terhadap Seni Patung Tradisional Di Desa Silakarang - I Wayan Mudana (Institut Seni Indonesia Denpasar, 2007)
statue work of art produced by artists at the village of Silakarang is traditional work of art this is raised as a problem highlighting the existence and impact of traditional statue work of art produced by statue artists in the village of Silakarang. The aims of this study are to see the development traditional statue work of art and its existence if compared with modern statue. This study took twenty kinds consisting for sample of 10 traditional statue and 10 modern statue and 30 respondent of stone carver who were divided into three groups, group A,B, and C. They were all used as sample using “ Purposive Sampling”. Data collection used observation technique, interview, documentation, and library research. The study employed descriptive analysis, that is, analysis technique analyzing the existence of traditional status work of art in four aspects: form, function, significance and marketing and analysis with impact; esthetic, social and culture, economic, and environmental.